Vivências de mulheres-primíparas nas práticas de cuidado ao parto vaginal - Scarton, Juliane (2015)
The birth is one of the major events in women's lives, because it establishes the transition to motherhood. In this sense, although the birth of a child usually be one of happiness overflowed event, one can not ignore that commonly this also constitutes a time of anxiety and fear determined by the experience of something unknown. To that end, all the attention in the birth process, from the beginning of labor, should be carried out taking into account the respect in the relationship between work, laboring woman and family. Based on the above, this study was guiding question "how was the experience of women-primiparous regarding care practices performed by nursing professionals during labor and delivery in a hospital in the state of Rio Grande South / Brazil? ", the objective was to know the experience of women-primiparous regarding care practices provided by nurses in labor and delivery. It was a field research, a qualitative approach with descriptive approach, performed in a maternity hospital in the interior of Rio Grande do Sul State, with ten women-gilts. Data production was due to the use of semi-structured interview, recorded in full, and the transcribed data and, subsequently, analyzed by qualitative analysis following the Proposal Operations. The ethical principles were observed under Resolution number 466/2012. This research was approved by the Research Ethics Committee, under the General Certificate of Appreciation for Ethics CAEE 26452313.8.0000.5346. Among the results emerged, care practices relating to non-pharmacological methods and evaluation of maternal and fetal well-being. Highlights included the active participation of nursing professionals, showing the present, concerned and helpful to the needs of women and also guided care in the clarification and guidance on how to proceed in the second stage and how to face the pain of uterine contractions in labor and delivery. On the other hand, it was found, the water and food restriction and routine performance of unnecessary procedures and without scientific evidence by nursing professionals. Moreover, it was found that professionals remained indifferent to the moment experienced by the woman and her family. In conclusion, the experience of care played by nurses in labor and delivery in attention to women-primiparous is intrinsically linked to the way the professional plays his care. It is hoped that this study will contribute in the care given to women in labor and delivery, through reflection and reformulation care behaviors in this area, both in hospitals and in the construction of knowledge on the subject in educational institutions, order to be consolidated from the needs of the key players involved in the birth scene, ie women, their babies and their families.